2015
DOI: 10.1080/02667363.2015.1022818
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the sight vocabulary and reading fluency of children requiring reading support: the use of a Precision Teaching approach

Abstract: This article outlines the impact of an eight-week Precision Teaching (PT) intervention on the sight vocabulary, reading fluency and reading attainment scores of a group of Irish primary school pupils. This study also sought to evaluate the role of PT in facilitating formative assessment of pupils' progress. Employing a mixed-method approach, this study comprised a quasi-experimental design and qualitative interviews involving 40 Irish primary school pupils and seven Learning Support Teachers. Following interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…One such intervention, which is readily available to schools, is Precision Teaching (Lindsley 1995). Recent research suggests that Precision Teaching can have motivational benefits and increase self-esteem, as well as being highly effective for teaching literacy skills (Griffin and Murtagh 2015).…”
Section: Discussionmentioning
confidence: 99%
“…One such intervention, which is readily available to schools, is Precision Teaching (Lindsley 1995). Recent research suggests that Precision Teaching can have motivational benefits and increase self-esteem, as well as being highly effective for teaching literacy skills (Griffin and Murtagh 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As PT seems to meet all the quality indicators identified in the literature, it may be a valuable approach to academic instruction for students with special educational needs. Several studies of PT have demonstrated improvements in the areas of literacy (Cavallini et al 2010;Datchuk et al 2015;Griffin and Murtagh 2015;Hughes, Beverley, & Whitehead, 2007), and numeracy (Chiesa & Robertson, 2000;Fitzgerald & Garcia, 2006;Greene, McTiernan, & Holloway, 2018;McTiernan, Holloway, Leonard, & Healy, 2018). However, as a recent systematic review highlighted, despite encouraging evidence, there is still a need for more research on the application of PT to students with IDDs (Ramey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of PT and fluency literature focuses on education and academic skills (Berens et al, 2003;Brady & Kubina, 2010;Brosnan et al, 2018;Cavallini & Perini, 2009;Chiesa & Robertson, 2000;Griffin & Murtagh, 2015;Carl Hughes et al, 2007;Lambe, Murphy, & Kelly, 2015;McDowell & Keenan, 2001;McTiernan et al, 2016;Mercer, Campbell, Miller, Mercer, & Lane, 2000;Milyko, Berens, & Ghezzi, 2012;Newsome et al, 2014;Sleeman, Friesen, Tyler-Merrick, & Walker, 2019). Research on nonacademic skills is small by comparison and limited to a handful of studies on fine-motor behavior and sports (Fabrizio, Schirmer, King, Diakite, & Stovel, 2007;Lokke et al, 2008;McDowell et al, 2002;Twarek et al, 2010;Weiss et al, 2010).…”
Section: Precision Teaching Researchmentioning
confidence: 99%